Efficient three time slots tdma-based protocols using inter-relay communication - Imran Ullah, Khan (Universiti Malaysia Sarawak (UNIMAS), 2014)
The mobile radio channel suffers due to fading effects during transmission of data from source to destination. In order to mitigate fading, diversity communication is used to send the same data over independent fading paths (diversity branches). There are some common techniques such as micro diversity, macro diversity, space diversity, frequency diversity and time diversity, which are used at receiver to achieve diversity communication. These diversity techniques tend to increase the size, complexity and the total power of the wireless network devices. To solve these issues cooperative diversity wireless communication has been introduced recently. In cooperative diversity wireless communication, diversity is achieved due to cooperation among users or relays. Different multiple access techniques have been proposed by various researchers, to achieve high diversity order at destination. Moreover, different two time slots and three time slots Time Division Multiple Access (TDMA) based Amplify-and-Forward (AF) protocols have been proposed by various researchers, in order to achieve high diversity order at destination. However, the low diversity order at the destination and low broadcasting degree at the source reduces the performance of these protocols and has several limitations.